Jogos Escolares do Paraná: análise da competiço no Município de Curitiba - Costa, Isabelle Plociniak (2017)
This study is focused on the participation of students in the city of Curitiba in the Paraná School Games, in order to discuss the effectiveness of these competitions as a public policy or just as a governmental policy. The research, which is documentary, exploratory, and descriptive, is based on data and information about collective sports disciplines from 2004 to 2013, except for 2010 and 2012, provided by the Regional Nucleus of General Education in Curitiba. Futsal and volleyball are more popular, but it is clear that students prefer futsal. Thus, it is important to understand that School Games do not represent an effective public policy due to the difference between their objectives and what really happens